Need dissatisfaction and its consequences on support for anti-pandemic behaviors in China: The mediation of attribution and local government satisfaction, and the moderation of social class - Zhang, Yan; Wang, Junxiu (Frontiers in Psychology, 2022)
The COVID-19 pandemic has greatly impacted the global economy, resulting in a substantial increase in inequality. There is a need to understand need dissatisfaction in this context, its group differences, and its consequences on support for anti-pandemic behaviors. Using data from a survey round of the Chinese Social Mentality Survey from April 21–May 6, 2022, 6,022 participants aged between 18 and 70 years (M = 32.27; SD = 8.74; men = 46.76%) from 29 provinces of Mainland China were included in the study. The results showed that need dissatisfaction was negatively related with support for anti-pandemic behaviors and was completely mediated by attribution and local government satisfaction. Internal/external attribution acted as a double-edged sword: they were negatively/positively related with support for anti-pandemic behaviors, while they became positively/negatively related with support for anti-pandemic behaviors via the mediation of local government satisfaction. People who were unemployed and in the subjectively middle class reported higher need dissatisfaction and less support for anti-pandemic behaviors compared to their counterparts. Social class moderated the relationship between need dissatisfaction and internal attribution: when needs were dissatisfied, participants with higher income and subjective social class tended to attribute more internally. This study contributes to the attribution theory and social identity theory in the context of major global public health events and provides practical implications for promoting behavioral compliance in the context of COVID-19. In particular, facilitating a positive interaction between the public and local governments may be helpful to create a shared identity and, ultimately, prevent and control the pandemic together.